Technical Fundamentals for All Levels - Gerbrands, T. (The Coach, 1998)
Many coaches think that fundamentals are only for those who start their volleyball career. In fact everyone needs elementary drills to raise perfection and ball control. So each player has to practice volleyball fundamentals as basic exercises (even international top-players practice them a few hours every week). The players of the Dutch national team are very familiar with the following examples. The exercises are useful for players at lower levels too, if the tasks are adapted according to the individual abilities.